Removal of nickel from aqueous solution by using dried water hyacinth (Eichhornia crassipes) - Norhaslin, Hashim (2008)
Biosorption has emerged as a new technology compared to classical method like chemical precipitation for removal metal from aqueous solution. In this present study, a dried Water Hyacinth (Eichornia Crassipes) was used as a biosorbent for Ni (II) removal from aqueous solution. The removal characteristics of nickel by dried Water Hyacinth were evaluated as a function of biosorbent dosage, contact time , pH and temperature . The percent Ni(II) uptake was analyzed by using Atomic Absorption Spectrophotometer. At optimal conditions, nickel uptake increased when biosorbent dosage increased. In this study, the optimum dosage was obtained at 0.3g. Removal of Ni (II) was more than 90% in 50 min of contact time. Removal of Ni (II) using dried Water Hyacinth is highly pH dependent. Within the tested pH range (pH 2-8), the maximum removal of Ni(II) was observed between pH 6 . The maximum removal of Nickel is at T= 35 oC. Result indicates that dried Water Hyacinth is suitable for the removal of nickel from aqueous solution.